ASSESSMENT OF SERUM ALARIN LEVELS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Kilinc, F.; Demircan, F.; Gozel, N.; Onalan, E.; Karatas, A.; Pekkolay, Z.; Ozdemir, F. A. (Editura Acad Romane, 2020)
Objective. We aimed to investigate the potential relationship between plasma alarin levels and type 2 diabetes mellitus (T2DM). Patients and Method. We included 154 participants, divided into four groups in a cross-sectional study design. The first group includes patients with T2DM without complications (n=30), the second group patients with T2DM with microvascular complications (T2DM-noC n=32), the third group patients with T2DM with macrovascular complications, T2DM-MV (n=32) and the last group is the healthy control group (n=60). Results. In our study 94 patients were diabetic; 47 females and 47 males. The control group consists of 60 people. 30 women and 30 men. It was found that these had a significant (p>0.05) variation in serum alarin levels among the T2DM (T2DM-noC=3.1 +/- 0.7 ng/mL T2DM-mV=2.8 +/- 0.4 ng/mL, T2DM-MV= 3.6 +/- 0.4 ng/mL) versus control group (15.6 +/- 2.6). We failed to find a sign want variation of serum alarin levels (p>0.05) between T2DM subgroups. Serum alarin levels were significantly higher among control patients (p<0.05). There was no difference between diabetic sub-groups. Conclusion. We concluded that serum alarin levels in patients with T2DM are lower than in normal people. Further studies are needed to investigate the possible prognostic value of alarin in clinical practice in T2DM.
Keywords: Type 2 diabetes mellitus; diabetic complications; alarin level